Integrating maternal depression care at primary private clinics in low-income settings in Pakistan: A secondary analysis - Owais, Syeda Somyyah; Horner, Ronnie D.; Khan, Muhammad Amir; Kenison, Kelli; Probst, Janice C. (Frontiers in Global Women's Health, 2023)
Background The prevalence of depression among women in Pakistan ranges from 28-66%. There is a lack of structured mental healthcare provision at private primary care clinics in low-income urban settings in Pakistan. This study evaluated a facility-based maternal depression intervention at private primary care clinics in low-income settings. Methods A mixed methods study was conducted using secondary data from the intervention. Mothers were assessed for depression using the Patient Health Questionnaire-9 (PHQ-9). 1,957 mothers (1,037 and 920 in the intervention and control arm, respectively) were retrieved for outcome measurements after one year of being registered. This study estimated the effectiveness of the depression intervention through cluster adjusted differences in the change in PHQ-9 scores between the baseline and endpoint measurements for the intervention and control arm. Implementation was evaluated through emerging themes and codes from the framework analysis of 18 in-depth interview transcriptions of intervention participants. Results Intervention mothers had a 3.06-point (95% CI: -3·46, -2·67) reduction in their PHQ-9 score at the endpoint compared to the control. The process evaluation revealed that integration of structured depression care was feasible at primary clinics in poor urban settings. It also revealed the gaps in public-private care linkage system and a need to improve referral systems. Conclusions Depression care at primary care level can be effective in reducing maternal depression. Clinic assistants can be trained to identify and deliver key depression counseling messages. Clinical Implications The study invites policy makers towards an opportunity to implement monitoring mechanism towards standard mental health care.